Action Research in Public Highway Organization for Developing a Learning Organization - Sookbumroong, Wisoot; Tanpichai, Prasong; Traimongkolkul, Pongpan (Kasetsart Journal of Social Sciences, 2011)
This action research aimed to develop a learning organization and enhance performance potential in a public highway organization. The concepts of organization development, learning in an organization, and knowledge management were integrated in the design of the research which was conducted based on the Uttaradit Highway District 1 organization. In respect of the organizational context, the research findings identified that the organization's infrastructure in terms of its systems and structures, leadership, communication, and culture supported a desirable learning atmosphere in the workplace. However, knowledge management practices had never been implemented in this highway district. Regarding the organization development process, the director, personnel, and community of practice (CoP) all participated in the following learning processes. 1) On awareness building and planning, the organization started knowledge management activities from a simple task by examining the work routine problems and explored the CoP in the office. 2) On action, the CoP members collaborated in thinking, trying out, and putting knowledge into action. 3) Lastly, on conclusion and reflection, the organization members viewed knowledge management as simple, practical, and applicable for enhancing organizational performance. With regard to research outcome, their constructed knowledge on "grass trimming" could be used to effectively resolve a problem and thus improve the job, as indicated by the CoP members' satisfaction.